Stereoselective Synthesis of (–)-Cinmethylin - Hasegawa, Kakeru; Ogawa, Narihito (Synlett, 2025)
We synthesized optically active (–)-cinmethylin with a high stereoselectivity. Sharpless asymmetric dihydroxylation of g-terpinene afforded an optically active diol with 98% ee. This diol was converted into (–)-cinmethylin in seven reaction steps. Dehydroxylation by the Barton–McCombie method was applicable, depending on the type of substituent, with the reaction affording the desired product when the substrate bore an OTBS group, but not when the substrate contained a benzyl ether. Decarbonylation gave the desired product regardless of the type of substituent. Furthermore, the stereoselectivity of the epoxidation reaction of an olefin with m-CPBA depended on the substituent, and up to 31% of the desired epoxide was obtained. Cyclization of the epoxide with PPTS proceeded with a good yield.
Keywords: cinmethylin; asymmetric synthesis; stereoselective synthesis; Sharpless asymmetric dihydroxylation; epoxidation; cyclization